A difusão do ideário escolanovista em grupos escolares sergipanos (1934-1961) - Almeida, Anne Emilie Souza de (2009)
The present study has as its objective analyzing the process of diffusion of the ideário" of the New School in the daily of school groups from Sergipe, from1934 until the year of 1960. Based on the perspective of New Cultural History, it searched theoretical endorsement in the workmanships of Lourenço Filho, Marta Carvalho, Zaia Brandão and Clarice Nunes. The sources of research for this study had been the terms of visit and the bulletins of inspection, acts of the pedagogical meetings, periodicals, legislation, amongst other sources. The school groups chosen for the related study were the School Group Dr. Manoel Luis , João Fernandes de Brito and the Gumercindo Bessa . The escolanovista ideário was spread out in the courses of formation of teachers, in the work of school overseers and in pedagogical meetings in daily of school groups, a procedure established in the Regulation 262, of October of 1945, a ruling document of the Public Instruction from Sergipe. From this process of diffusion it had protruded the work of some intellectuals as Helvécio de Andrade, Rocha Lima, Nunes Mendonça and Acrísio Cruz.